By executive order : bureaucratic management and the limits of presidential power - Rudalevige, Andrew, 1968- (Princeton University Press, 2021)
In this book, Andrew Rudalevige examines more than five hundred executive orders from the 1930s to the present today (as well as more than two hundred others negotiated but never issued) shedding light on the multilateral process of drafting supposedly unilateral directives. He draws on archival evidence from the Office of Management and Budget and presidential libraries as well as original interviews to show how the crafting of orders requires widespread consultation and compromise with a formidable bureaucracy. Rudalevige explains the key role of management in the presidential skill set, detailing how bureaucratic resistance can stall and even prevent actions the chief executive desires, and how presidents must bargain with the bureaucracy even when they seek to act unilaterally.